Season fluctuations of level of 25-hydroxycholecalciferol in pregnant women living in Saint Petersburg - E L Khazova; L V Shirinyan; I E Zazerskaya; V A Bart; E Yu Vasilieva (IP Berlin A.V., 2015)
In this article there are shown cohort prospective research results of 25-hydroхуholecalciferol level estimation in blood serum during pregnancy among women depending on the season of the year. The aim of this research is to estimate the intensity of the body of pregnant women with vitamin D in different seasons during pregnancy, who live in Saint Petersburg. There are involved 205 pregnant at I trimester. It was finished by 192 patients. All patients were divided into 4 subgroups depending on the season of the year while involving to the study. At 12-14 weeks there was first blood sampling. From the I trimester till delivery all patients took 500 IU of сolecalciferol contained in multivitamin complexes. During pregnancy 25-ОН-D level in blood serum was measured at 12-14, 24-26, 34-36 weeks of gestation. There are not found significant differences of the initial mean level of 25-ОН-D in all pregnant (17.5, 21.3, 22.6, 19.9 ng/ml, accordingly to the 1st, 2nd, 3rd and 4th subgroups). It was defined the maximal intensity of vitamin D at I trimester of pregnancy during summer - 22.6 ng/ml, which refers to the criteria of vitamin D insufficiency. Minimal concentration of 25-ОН-D among subgroups was revealed during winter - 17.5 ng/ml, which refers the criteria of vitamin D deficiency. Total concentration of 25-ОН-D authentically does not differ between subgroups. The increase the level of 25-ОН-D from the I to the III trimester takes place regardless of the season. The study showed no significant changes in the level of 25-OH-D in blood serum of pregnant depending on the season.